Spatial concepts of Lithuania in the long nineteenth century - Staliūnas, Darius (2016)
"This book deals with the spatial concepts of Lithuania and other geo-images that either 'competed' in the nineteenth century with the term Lithuania or were of a different taxonomic level (Samogitia, Prussia's Lithuania, Lithuania Minor, Poland, the Western region, the Northwest Region, Lita/Lite, Belarus, East Prussia etc.). The Russian, Lithuanian, Polish, Belarusian, Jewish, and German geo-images of this territory are analyzed in separate chapters of this volume. The spatial and topographical turns, especially the innovative perspective suggested by French Marxist Henri Lefebvre to look at the (social) space as a product of social creativity, research on so-called mental maps, postcolonial studies, and nationalism studies provided some theoretical background as well as analytical approaches for the studies published in this volume"...Provided by publisher